Is Inheritance System a Factor in the Care of AIDS Orphans? The Asante and Krobo of Ghana Scenario - Yarney, L.; Mba, C.; Asampong, E.; Darko, J.; Yarney, J. (My University, 2012)
Background Almost three decades after the discovery of HIV and AIDS in Ghana, the most obvious impact of the disease is the growing orphan crisis affecting most families and communities, especially in areas that the prevalence of HIV has exceeded the epidemic’s threshold of 5%. Studies have indicated that these orphans usually experience a wide range of problems which include education, nutrition, physical and sexual abuse, emotional and psychological distress, stigma and discrimination, among others The aim of the study was to examine the social, cultural, and traditional norms and practices that influence the care of children orphaned by AIDS in Ghana. Methods The study employed focus group discussions, in-depth interviews and key informant interviews to generate information on the socio-cultural factors that impact orphan care in the Ashanti and Eastern regions of Ghana. Results The findings indicated that the cultural practices that influence how well an AIDS orphan is taken care of by their caregivers include traditional rituals, ceremonies, and norms like funeral rites, marriage and naming ceremonies, festivals, inheritance, polygyny, and puberty rites. The social factors mentioned to affect orphan care significantly were: excessive alcohol drinking, and tobacco and drug use, dressing with fashion, night club attendance, market days, stigma and discrimination, among others. Conclusion It is recommended that though some cultural and traditional practices are deeply rooted in communities and cannot be done away completely, orphan care policies on interventions should take into account these factors to mitigate their effects on the care of orphans.